The Role of the Former combatants’ reintegration on promotion of inclusion and equity in Mt. Elgon region, Kenya (International Journal of Scientific Research and Management (IJSRM), 2018)
The social reintegration of former combatants is the most important aspect of the disarmament, demobilization and reintegration (DDR) process. Post conflict societies are marked by their past traumas long after the interest of most outsiders has ebbed. Reintegration understood in this context, speaks to societal transformation, which both takes time and is prone to setbacks long after peace has formally been declared. The purpose of the study was to investigate the role of reintegration of former combatants on promotion of inclusion and equity. The objective of the study was to explain the role of the former combatants’ reintegration on promotion of inclusion and equity in Mt. Elgon region. The desistance theory was used in the study. The study used the cross sectional descriptive survey design. The population of the study comprised former combatants, Sub County Commissioners, peace committee members, religious leaders and NGOs. The respondents comprised former combatants, sub county commissioners and peace committee members, religious leaders and NGOs. The stratified and purposive random sampling technique was used to select a sample of 150 former combatants, Three Sub County commissioners and 16 peace committee members, five religious leaders and Four NGO members. Data was collected by use of questionnaires, interviews and Focus Group discussion. In order to ascertain validity, the questionnaires and interview schedules were given to experts who matched all the items with the research questions to ascertain whether the instruments would measure all that it is supposed to measure. The reliability of the instruments was determined through test retest of the instruments. Data was analyzed by use of descriptive statistics of frequencies and percentages. Data from in-depth interviews was audio taped and transcribed. The transcripts were then organized into themes and categories as they emerged from the field. The findings of the study were presented descriptively. The findings of the study showed that: in the context of social reintegration the three dimensions of family and community; sustainable employment; and civic responsibilities should be given proper attention: to achieve the goal of reintegration there should be a major shift in the contemporary DDR approach by moving from the insertion approach towards a social reintegration one; community support is essential for the successful reintegration of former combatants and the sustainable social and economic reintegration of former combatants should be the ultimate objective of disarmament and demobilization and reintegration (DDR). Consequently, the study recommends that the government should budget for and give priority to the reintegration programmes so that they are fully completed instead of leaving them at the reinsertion stage; the communities take the lead in proposing community- based solutions for the issues identified.